Verb phrase and its grammatical categories - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article examiners structural discordances in English and Uzbek by providing specific examples of differences and similarities between the two languages. We will study how to employ grammatical categories of verbs in both languages in this post.